Structural analysis of the sugar and ethanol sector of the Valle del Cauca - Cruz Aguilar, Pedro (Cuadernos de Administración, 2010)
Analysis of the sector tries to demonstrate that following the international price of sugar above 16 cents a pound, the sugar industry will count on coordinating mechanisms that will allow them to direct their production of cane sugar to the link in the productive chain which will produce the greatest profit margin will produce, without having to increase the number of acres planted in proportion to the increase in sugar exported. This consolidated the sugar industry as one of the driving forces of the Colombian economy, but to date has forced the government to lower the percentage of ethanol fuel in gasoline from 10 to 8 percent and casts doubt on the implementation of decrees which substantially increase the percentage of alcohol fuel for engines of 2000 cms3